Abiotic Stress Responses in Plants 2011
DOI: 10.1007/978-1-4614-0634-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Increasing Salt Tolerance in Crop Plants

Abstract: Soil salinity is widely recognized as a major threat to global food security. Salinity and other abiotic stresses, which are expected to be more frequent in future due to disturbances in global climate, pose a serious challenge for plant scientists to ensure food supply for the growing world population. Several approaches have been advocated to address the salinity problem, but the most logical solution to maintain crop productivity in salt-affected areas is to enhance salt tolerance of crop plants. Due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 166 publications
0
7
0
1
Order By: Relevance
“…). Genetic variation in leaf Na + and K + /Na + ratio indicates the possibility of genetic improvement of salt tolerance (Karan & Subudhi ). Sufficient genetic variations for leaf Na + contents and K + /Na + ratio were found in this panel.…”
Section: Discussionmentioning
confidence: 99%
“…). Genetic variation in leaf Na + and K + /Na + ratio indicates the possibility of genetic improvement of salt tolerance (Karan & Subudhi ). Sufficient genetic variations for leaf Na + contents and K + /Na + ratio were found in this panel.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Karan & Subudhi (2012) essa planta possui capacidade de adaptação a uma vasta gama de fatores climáticos, topográficos e edáficos.…”
Section: Introductionunclassified
“…Our study demonstrated large variation in various parameters among different wheat varieties at seedling stage under salinity stress ( Table 1 ). The salt-tolerance index was employed for GWAS, as it is considered a reliable measure for assessing salt tolerance, which permits the control for background effects among different genotypes ( Karan and Subudhi, 2012 ; Long et al, 2013 ; Kan et al, 2015 ). Significant genetic variations for the agronomic traits measured and shoot Na contents and Na/K ratio in this panel indicated the possibility of genetic improvement of salt tolerance ( Yong et al, 2015 ; Oyiga et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%